Analysis of true triaxial mechanical behavior and energy dissipation of backfill under different unloading rates - Xiaofei LI; Jiajian LI; Yunpeng KOU; Weidong SONG (工程科学学报)
Recent advancements in mining technology have led to the widespread adoption of the cut-and-fill stoping method in metal mines due to its effectiveness in controlling ground pressure, minimizing surface settlement, and reducing tailings discharge. Backfill serves as a core component of this method, and its mechanical behavior and stability directly influence the safety and efficiency of mining operations. This study investigates the effect of unloading rate on the mechanical behavior of backfill and its destabilization and damage mechanisms in complex stress environments. True triaxial unloading tests were carried out on backfill specimens under four different unloading rates: 3, 4, 6, and 8 kPa·s−1. The loading and unloading processes were independently controlled along three principal stress directions (σ1, σ2, and σ3). In addition, the energy dissipation characteristics of backfill under different unloading rates were analyzed based on the energy dissipation principle. CT scanning was performed to obtain the three-dimensional distribution and morphology of internal cracks within the backfill, followed by quantitative crack analysis using image analysis software. Key experimental parameters include axial stress and strain, elastic and dissipative energy, three-dimensional crack reconstruction, and crack distribution curves along the σ1, σ2, and σ3 directions. The results indicate that the stress state within the backfill changed significantly during unloading. As the unloading rate increased, the stress redistribution within the backfill intensified, leading to a decrease in axial peak stress, an increase in the dissipated energy at the peak stress point, and greater structural damage. The mechanism by which the unloading rate affects the true triaxial mechanical behavior of the backfill is as follows: As the unloading rate increases, the stress redistribution within the backfill becomes more intense. Unloading results in the rapid release of stress, causing the backfill to experience large stress changes within a relatively short period. This resulted in reduced peak axial stresses, increased damage, and the formation of unloading cracks in the backfill at higher unloading rates. In practical engineering applications, variations in stress characteristics significantly affect backfill stability. A high unloading rate can lead to sudden backfill failure, increasing the risk of surface subsidence or mine accidents. Proper control of the unloading rate reduces energy dissipation and improves backfill stability. Optimizing backfill material composition and construction techniques based on expected discharge rate is essential to maintaining structural backfill stability during mining. In addition, optimizing the mining sequence allows for effective unloading rate control, reducing ground pressure activity and mitigating backfill damage caused by rapid unloading. Strategies such as stepwise mining and gradual unloading have been employed to address these challenges. This study provides a scientific basis for optimizing mine design and improving mine safety.